2017
DOI: 10.21849/cacd.2017.00052
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Conversational Language Samples and Norm-Referenced Test Scores

Abstract: Research demonstrates that many speech-language pathologists (SLPs) do not routinely include language sample analysis (LSA) in their clinical practice because LSA has limited recognition as a valid assessment measure. Limited research suggests that some LSA values obtained from narrative samples correlate with the results of standardized language tests. This research examined the relationship among values obtained from conversational language samples and the results of standardized testing. Methods: This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Another interesting finding of this study was that correlations between a standardized assessment tool (the PLS-5) and LSA were moderate at best. While some studies have found similarly weak correlations-including insignificant correlations-between LSA and standardized assessment tools (Ebert & Scott, 2014), others have found stronger relationships (Owens & Pavelko, 2017), at least for some measures. However, our results were more congruent than those of previous studies that contrasted standardized assessment with LSA in the preterm population (Crosbie et al, 2011;Imgrund et al, 2019;Mahurin-Smith et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Another interesting finding of this study was that correlations between a standardized assessment tool (the PLS-5) and LSA were moderate at best. While some studies have found similarly weak correlations-including insignificant correlations-between LSA and standardized assessment tools (Ebert & Scott, 2014), others have found stronger relationships (Owens & Pavelko, 2017), at least for some measures. However, our results were more congruent than those of previous studies that contrasted standardized assessment with LSA in the preterm population (Crosbie et al, 2011;Imgrund et al, 2019;Mahurin-Smith et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
“…The relationship between classifications was determined by identifying participants who were 1.5 SDs below the mean PLS-5 Total Language Score, MLUm, and TNW of the term-born children included in our study. MLUm and TNW were selected to represent morphosyntactic and lexical ability because they have been used in previous studies as primary outcomes of LSA (Owens & Pavelko, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…studied differences in sample length in minutes and found that short samples of TD children yielded reliable measures of productivity, lexical diversity, and utterance length. As already mentioned in the introduction, several studies have tried to reduce time for LSA (Owens & Pavelko, 2017;Pavelko et al, 2020;Wiegers, 1996). However, most of these studies concerned (young) TD children.…”
Section: Discussionmentioning
confidence: 99%
“…Stipdonk et al (2020) assessed very preterm (<32 weeks) children and full-term children and analyzed the relationships between six item-based subtests and MLU, but only those that focused on skills at the sentence level (three) reached a statistically significant relationship with MLU. Owens and Pavelko (2017) purposely chose three subtests that elicited responses in sentence format to analyze the relationships with MLU, which proved statistically significant. This pattern of results, in which statistically significant associations are more frequent at the sentence level than at the word level, makes sense because MLU involves the production of sentences.…”
Section: Comparison Between Standardized/item-based Tests and Narrati...mentioning
confidence: 99%